Offender risk assessment practices vary across Canada - Bourgon, Guy (Canadian journal of criminology and criminal justice, 2018)
The dominant Canadian approach to offender rehabilitation, the risk-need-responsivity (RNR) model, requires assessing offenders’ likelihood of recidivism and their criminogenic needs (i.e., risk/need assessments). The current study examines the risk/need assessments routinely used in Canadian corrections and compares their risk category labels. All Canadian jurisdictions used a risk/need tool for general recidivism, most used sex-crime-specific tools, and a few used tools specific to intimate partner violence. There was, however, considerable diversity in the names, number, and meaning of the risk category labels, which could result in different responses to the same individual based [End Page 167] solely on the version of the risk tool used in any specific jurisdiction. Our results suggest that increased attention to the meaning of risk category labels could facilitate offenders receiving the most appropriate and fair correctional responses.